(untitled) (Journal of the College of Basic Education, 2019)
Objective: DMT 2 is the common metabolic disorders with highly impact on quality of life. The tsability of C. Spinosa fruits extract in reducing plasma glucose levels and serum lipids was tested . There is no study about the anti-diabetic , anti- obesity effect of capparis spinosa fruits in Iraq . Therefore, we aim to study the effects of the C. spinosa fruits on diabetic obese patients.